Effect of Surfactant Addition on The Physico-Chemical Properties and Stability of Virgin Coconut Oil Nanoemulsions - Linda Trivana; Nugraha E. Suyatma; Dase Hunaefi; S. Joni Munarso (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
Virgin coconut oil (VCO) is high quality coconut oil and categorized as the healthiest oil and functional foods. Based on these benefits, the development of a VCO in emulsion product might increase the human consumption of coconut oil because consumers dislike the only taste of pure VCO. The aim of this study was to develop the water compatible form of VCO through nano-emulsification. The effect of different types and amounts of surfactants (Tween 80 and Span 80) on the physio-chemical characteristic of emulsion containing VCO was investigated. VCO based emulsions were prepared with the aid of Ultra-Turrax homogenizer. Emulsions were developed by adding and mixing VCO with surfactants. The ratio of Tween 80 and Span 80 used were 0:10, 2.5:7.5, 5:5, 7.5:2.5, and 10:0. The droplet size of nanoemulsions consisting of Tween 80:Span 80 (0:10, 2.5:7.5, 5:5, 7.5:2.5, and 10:0) were 1.343, 0.606, 0.829, 1.439, and 2.506µm, respectively. Based on the TEM analysis and polydispersity index (PDI) >0.5 showed the oil droplets are in not uniform shape, indicating a unstable emulsion. VCO emulsion with ratio Tween 80:Span 80 (0:10) obtained a homogeneous emulsion (stable) compare than that of others and w/o type emulsion. The stability of emulsion is evaluated by turbidity measurement using UV-VIS spectrophotometer with wavelength 502 nm. A combination of treatments (ambient condition, thermal treatmeant (40°C)), and centrifuge) of VCO emulsion has resulted on thermal treat, the turbidity measured from the emulsion was higher than the other emulsion, reflecting the presence of the smaller droplets in this emulsion.